Counseling on Complementary Deep Slow Breathing Therapy to Reduce Anxiety and Pain in IUD and Implant KB Acceptors - Rini Astuti Damanik; Dewi Handayani; Beringin Jaya Munthe (Outline Journal of Community Development, 2024)
Contraception is a tool used to avoid or prevent pregnancy as a result of a meeting between egg cells and sperm cells. There are many types of contraceptives, one of the contraceptive methods with high effectiveness is the long-term method, namely the intrauterine device (IUD) and implant. UPT Puskesmas Medan Tuntungan Medan City is one of the primary health service centers that provides and provides free family planning services in its working area with still low levels of IUD and Implant use. The complaint that is often found by family planning acceptors is that when they want to use an IUD which is a foreign object, it creates a feeling of anxiety when installing it and many family planning acceptors don't choose the implant because they are afraid of how it will be installed. The aim of this activity is to reduce anxiety and pain before IUD and implant installation by using complementary therapies such as deep slow breathing relaxation. This service activity was carried out at the Medan Tuntung Community Health Center UPT Medan City Jl. Tani's Victory, Medan Tuntungan District, Medan City. Counseling on Complementary Therapy to Reduce anxiety and pain in IUD and Implant KB acceptors can understand and understand the benefits of complementary therapy and can carry out complementary therapy to reduce anxiety and pain in IUD and Implant KB acceptors properly and correctly at the Medan Tuntungan Community Health Center Village UPT.